(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This review summarizes evidence on the health and developmental benefits of breastfeeding. A systematic analysis of 147 studies (2014–2024) from major databases shows that exclusive breastfeeding for six months reduces infant mortality by 13%, lowers the risk of sudden infant death syndrome by 36%, and significantly decreases gastrointestinal and respiratory infections as well as allergic diseases. Breastfed children also demonstrate better cognitive development, with an average IQ increase of 3.2 points. These findings confirm breastfeeding as the gold standard for infant nutrition, providing optimal growth, strong immunity, and long-term neurodevelopmental advantages. Strengthening global lactation support programs is essential to improving population health.